Role of nitrogen doping in modulating ruthenium nanocatalysts for enhanced electrochemical hydrogen evolution reaction in alkaline medium - Korampattu, Lavanya; Barik, Sidharth; Pandikassala, Ajmal; Urkude, Rajashri R.; Kurungot, Sreekumar; Dhepe, Paresh L. (Chemistry of Materials, 2024)
Nitrogen doping has become a fundamental approach to enhance the catalytic performance of carbon materials across various applications. The introduction of nitrogen creates defects and active sites, promoting the formation of small metal particles and strengthening the metal-support interaction within carbon materials. However, the challenge lies in developing sustainable and cost-effective methods for synthesizing nitrogen-doped carbon materials. In this study, we present a sustainable approach for the synthesis of ruthenium on nitrogen-doped carbon catalysts (Ru-CCP) using chitosan as a nitrogen and carbon source. Unlike traditional methods, our process avoids the use of additional nitrogen precursors and templates, streamlining the synthesis while using a renewable resource. The synthesized material exhibits an exceptional performance in the electrochemical hydrogen evolution reaction (HER) in alkaline conditions by achieving a current density of 25 mA cm(-2) at an impressively low overpotential of 46 mV, outperforming Pt/C under similar conditions. The detailed studies on structural and electronic properties of the materials using X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and transmission electron microscopy (TEM) revealed that the remarkable catalytic activity is upheld by the unique interplay between Ru delta+ and surface nitrogen moieties, notably pyridinic and pyrrolic nitrogen. Here, we demonstrate the control of particle size and electronic environment around the metal atom via the interaction of nitrogen and unravel the role of nitrogen doping in tuning the catalytic performance. In addition, this work offers insights into efficient HER catalyst design and emphasizes the potential of biomass-derived materials like chitosan in advancing clean hydrogen production for renewable energy applications.

Shell waste valorization to chemicals: methods and progress - Korampattu, Lavanya; Ghosh, Neha; Dhepe, Paresh L. (Green Chemistry, 2024)
In light of growing energy and resource demands, the conversion of biomass materials into diverse chemicals and fuels holds significant importance. This process enables the utilization of biomass as a valuable and renewable resource to meet these escalating needs. The current biomass valorization processes are largely based on plant-derived lignocellulosic biomass materials. Studying new genres of biomass materials and their value addition is highly desirable, and they would complement and expand the existing biorefinery system. Crustacean shell waste represents a highly potential bioresource that is composed of a set of useful chemicals, among which chitin, the amino polysaccharide, has come to the fore as a promising material for a plethora of applications. In terms of the abundance of biopolymers on Earth, cellulose is the most prevalent biopolymer, and chitin ranks as the second. The presence of biologically fixed nitrogen in the structure of chitin opens up new possibilities for making useful chemicals, notably nitrogen-containing chemicals, which are otherwise impossible to produce directly from lignocellulosic biomass. In the last two decades, several attempts have been made by researchers in this area to convert chitin and its derivatives into valuable chemicals. This review comprehensively summarizes the transformation of the chitin fraction from shell waste to various chemicals through different thermo-catalytic processes and appraises the advancements in this area. The effect of various catalytic systems on chitin biomass valorization processes and the challenges and opportunities allied to this are discussed. This review summarises the thermo-catalytic processes converting chitin from shell waste into diverse chemicals and reviews the advances, catalytic systems, and associated challenges.

Chitosan-derived carbon supported ruthenium catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Korampattu, Lavanya; Dhepe, Paresh L. (Sustainable Energy & Fuels, 2025)
The transition from fossil fuels to sustainable energy and chemical production relies heavily on efficient biomass valorization. Levulinic acid (LA), a key platform chemical from lignocellulosic biomass, serves as a versatile precursor for valuable chemicals like gamma-valerolactone (GVL), a promising green solvent, fuel additive, and polymer precursor. While ruthenium-based catalysts are effective for LA hydrogenation, conventional systems like Ru/C often suffer from metal leaching and deactivation due to weak metal-support interactions. Current approaches to improve stability, such as using nitrogen-doped carbon supports, involve complex synthesis and synthetic nitrogen precursors. Addressing these limitations, we present a facile and sustainable strategy for synthesizing a robust ruthenium catalyst by directly pyrolyzing marine biomass-derived chitosan to form a self-nitrogen-doped carbon support. This catalyst exhibited superior stability and excellent recyclability in the aqueous-phase hydrogenation of LA to GVL, surpassing conventional Ru/C while maintaining activity comparable to that of leading Ru catalysts supported on N-doped carbon. Unlike other N-doped carbon supports, our method avoids synthetic N-dopants and tedious procedures, making it inherently more sustainable. Detailed characterization via XPS and H2-TPR revealed strong metal-support interactions, facilitated by intrinsic nitrogen functionalities, effectively stabilizing the ruthenium species. This study also identifies the critical role of graphitic and pyridinic nitrogen species in controlling catalytic activity and elucidates the importance of optimizing nitrogen species and content in tailoring chitosan-derived supports. The proposed mechanism describes how Ru-N centers activate hydrogen and LA, with basic nitrogen sites aiding the dehydration step to GVL. Overall, this work features the potential of chitosan derived carbon as a sustainable and tunable support for efficient biomass hydrogenation catalysts and offers fundamental insights into the role of nitrogen doping in tailoring catalytic performance.